Anticancer Diiron Vinyliminium Complexes: A Structure-Activity Relationship Study - Simona Braccini; Giorgia Rizzi; Lorenzo Biancalana; Alessandro Pratesi; Stefano Zacchini; Guido Pampaloni; Federica Chiellini; Fabio Marchetti (MDPI AG, 2021)
A series of 16 novel diiron complexes of general formula [Fe2Cp2(CO)(μ-CO){μ-η1:η3-C(R')C(R")CN(R)(Y)}]CF3SO3 (2-7), bearing different substituents on the bridging vinyliminium ligand, was synthesized in 69-95% yields from the reactions of diiron μ-aminocarbyne precursors with various alkynes. The products were characterized by elemental analysis, IR, 1H and 13C NMR spectroscopy; moreover the X-ray structures of 2c (R = Y = CH2Ph, R' = R" = Me) and 3a (R = CH2CH=CH2, Y = R' = Me, R" = H) were ascertained by single-crystal X-ray diffraction studies. NMR and UV-Vis methods were used to assess the D2O solubility, the stability in aqueous solution at 37 °C and the octanol-water partition coefficients of the complexes. A screening study evidenced a potent cytotoxicity of 2-7 against the A2780 cancer cell line, with a remarkable selectivity compared to the nontumoral Balb/3T3 cell line; complex 4c (R = Cy, Y = R' = R" = Me) revealed as the most performant of the series. The antiproliferative activity of a selection of complexes was also assessed on the cisplatin-resistant A2780cisR cancer cell line, and these complexes were capable of inducing a significant ROS production. Moreover, ESI-MS experiments indicated the absence of interaction of selected complexes with cytochrome c and the potentiality to inhibit the thioredoxin reductase enzyme (TrxR).